1995
DOI: 10.1074/jbc.270.11.6227
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Two Functionally Distinct Lysine-binding Sites in Kringle 37 and in Kringles 32−36 of Human Apolipoprotein(a)

Abstract: The well documented association between high plasma levels of lipoprotein(a) (Lp(a)) and cardiovascular disease might be mediated by the lysine binding of apolipoprotein(a) (apo(a)), the plasminogen-like, multikringle glycoprotein in Lp(a). We employed a mutational analysis to localize the lysine-binding domains within human apo(a). Recombinant apo(a) (r-apo(a)) with 17 plasminogen kringle IV-like domains, one plasminogen kringle V-like domain, and a protease domain or mutants thereof were expressed in the hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
97
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(106 citation statements)
references
References 63 publications
8
97
0
Order By: Relevance
“…Recently Ernst et al [34] performed similar studies, but they found K-4 T5-T9 to be crucial for an efficient assembly of Lp(a), especially K-4 T5, which we found to have no effect on the association of r-apo(a) with LDL. Without doubt further work will be necessary to resolve all the structural details of apo(a) that influence its assembly with LDL.…”
Section: Assembly Of Lp(a): the Role Of Apo(a) Structuresupporting
confidence: 61%
“…Recently Ernst et al [34] performed similar studies, but they found K-4 T5-T9 to be crucial for an efficient assembly of Lp(a), especially K-4 T5, which we found to have no effect on the association of r-apo(a) with LDL. Without doubt further work will be necessary to resolve all the structural details of apo(a) that influence its assembly with LDL.…”
Section: Assembly Of Lp(a): the Role Of Apo(a) Structuresupporting
confidence: 61%
“…10,11 To exclude the possibility that the observed noncovalent association of the apoB48-like species was the result of either sequence differences relative to plasma-derived apoB48 22 or differences in the composition of the lipid core, we assessed the binding of chylomicrons isolated from human plasma to either the KIV 5-8 or 17K Figure 2. Specificity of interaction of human LDL with r-apo(a)-Sepharose 4B affinity columns.…”
Section: Resultsmentioning
confidence: 99%
“…The total number of these binding sites would be unmasked in free apo(a) accounting for the marked differences in binding between apo(a) as a free standing unit and apo(a) as a constitutive component of Lp(a). This masking concept was previously invoked to explain the differences in binding between Lp(a) and apo(a) for lysine (10,42), fibrinogen (11,12), and fibronectin (12).…”
Section: Discussionmentioning
confidence: 99%
“…Our current studies have also provided evidence that the binding to decorin by apo(a) occurs via its C-terminal domain that comprises kringles IV-5 to IV-10, kringle V, and the protease region (12). This is the domain that contains the two previously identified lysine-binding sites, one of high affinity located in kringle IV-10, and the other of low affinity, comprising kringles IV-5 to IV-8 with their respective linkers (10,42). However, the fact that the binding of apo(a) to the protein moiety of decorin was not prevented by either lysine or the lysine analogue, EACA, suggests that neither of the two lysine- binding sites in apo(a) was directly involved in the binding, pointing at the potential participation of kringles IV-9, V, and the protease region and/or the corresponding linkers.…”
Section: Discussionmentioning
confidence: 99%